Learning landscape ecology : a practical guide to concepts and techniques - Gergel, Sarah E., 1969-; Turner, Monica Goigel (New York, NY : Springer New York, 2002)
Landscape ecology continues to grow as an exciting, dynamic ecological d- cipline. With its broadscale emphasis and multidisciplinary approach, la- scape ecology lends itself both to basic research and to applications in land management, land-use planning, wildlife management, ecosystem mana- ment, and conservation biology. Landscape ecology makes a unique cont- bution to the scientific community in its attention to ecological dynamics across a broad range of spatial and temporal scales, and as a result it has - come increasingly important for students in the natural sciences to gain a - sic understanding of the subject. Colleges and universities across the United States are incorporating courses in landscape ecology into their curricula. However, nearly every book on landscape ecology is a book to be read, la- ing a hands-on approach. This text is intended to fill that void by providing a comprehensive collection of landscape ecology laboratory exercises. These teaching exercises stress the fundamental concepts of landscape ec- ogy, rather than highly specialized, technical methods. While students will gain experience using a variety of tools commonly used in landscape ecology, we stress the conceptual understanding necessary to use these techniques app- priately. This book attempts to convey the myriad approaches used by la- scape ecologists (as well as a multitude of approaches to teaching) and include group discussion, thought problems, fieldwork, data analysis, spatial data c- lection, exposure to Geographic Information Systems (GIS), simulation m- eling, analysis of landscape metrics, spatial statistics, and written exercises.
and Concepts of Scale -- Scale and Hierarchy Theory -- Collecting Spatial Data at Broad Scales -- to Geographic Information Systems (GIS) -- Models and Causes of Landscape Pattern -- to Markov Models -- Simulating Changes in Landscape Pattern -- Creating Landscape Pattern -- Quantifying Landscape Pattern -- Understanding Landscape Metrics I -- Understanding Landscape Metrics II -- Neutral Landscape Models -- Scale Detection Using Semivariograms and Autocorrelograms -- Disturbance Dynamics -- Landscape Disturbance -- Alternative Stable States -- Organism Response to Landscape Pattern -- Interpreting Landscape Patterns from Organism-Based Perspectives -- Landscape Context -- Landscape Connectivity and Metapopulation Dynamics -- Individual-Based Modeling -- Ecosystem Processes at Broad Scales -- Feedbacks between Organisms and Ecosystem Processes -- Modeling Ecosystem Processes -- Applied Landscape Ecology -- Reserve Design -- Prioritizing Reserves for Acquisition.
Elektronická reprodukce.
Keywords: péče o životní prostředí; krajinná ekologie; územní rozvoj; územní plánování; environmental care; landscape ecology; territorial development; spatial planning; e-knihy online; e-books online